2016
DOI: 10.1515/pjfns-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Blood Glucose Lowering Efficacy of Strawberry Extracts rich in Ellagitannins with Different Degree of Polymerization in Rats

Abstract: In two experiments on rats it was analyzed whether the lowering rate of postprandial glycaemia depends on the degree of polymerization of strawberry ellagitannins (ET). Two types of highly-concentrated polyphenolic extracts were used, one rich in monomeric ET (ETM; 94.9% polyphenols and 67% ETM in it), the second in dimeric ET (ETD; 95.9% polyphenols, and 78.0% ETD in it). The experiment 1 comprised three oral sugar tolerance tests, GTT (with glucose; to examine monosaccharide transport across epithelium), SuT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…There is increasing evidence that polyphenolic compounds, especially ellagitannins, from plants can cause insulin-like effects on glucose utilization [ 39 , 40 , 41 ]. Earlier, the ability of dimeric ellagitannins from strawberry extract to reduce elevated blood glucose was shown [ 42 ]. In this connection, we decided to estimate the hypoglycaemic activity of C. palustre extracts (A and B) and evaluate the same activity for the predominant dimeric ellagitannin agrimoniin.…”
Section: Resultsmentioning
confidence: 99%
“…There is increasing evidence that polyphenolic compounds, especially ellagitannins, from plants can cause insulin-like effects on glucose utilization [ 39 , 40 , 41 ]. Earlier, the ability of dimeric ellagitannins from strawberry extract to reduce elevated blood glucose was shown [ 42 ]. In this connection, we decided to estimate the hypoglycaemic activity of C. palustre extracts (A and B) and evaluate the same activity for the predominant dimeric ellagitannin agrimoniin.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that even a small change in the chemical structure of a molecule is of paramount importance to its biological activity in the host’s body [ 10 , 11 , 12 ]. Our recent study showed that the separate mechanisms leading to decreased postprandial glycaemia upon dietary administration of strawberry ETs largely depends on their chemical structure, i.e., degree of polymerization [ 13 ]. In the study on rats it was presented that extract with monomeric ETs was mitigated the glucose- or sucrose-induced postprandial glycemic load more beneficially than extract with dimeric ETs [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent study showed that the separate mechanisms leading to decreased postprandial glycaemia upon dietary administration of strawberry ETs largely depends on their chemical structure, i.e., degree of polymerization [ 13 ]. In the study on rats it was presented that extract with monomeric ETs was mitigated the glucose- or sucrose-induced postprandial glycemic load more beneficially than extract with dimeric ETs [ 13 ]. Another study by Jurgoński et al [ 14 ] showed strong antibacterial activity of a dietary combination of monomeric strawberry ETs with fructooligosaccharides (FOSs) in the rat cecum, and this effect was not observed with dimeric ETs or in treatments without FOSs.…”
Section: Introductionmentioning
confidence: 99%
“…Ellagitanins from strawberry pomace decreased postprandial glycaemia in rats by mitigated glucose-, starch-or sucrose-induced postprandial glycemic load. It also decreased the activities of mucosal sucrose and maltase in the jejunum [105].…”
Section: Strawberrymentioning
confidence: 92%